Mycobacterial Aminoglycoside Acetyltransferases: A Little of Drug Resistance, and a Lot of Other Roles - Sanz-García, Fernando; Anoz-Carbonell, Ernesto; Pérez-Herrán, Esther; Martín, Carlos; Lucía, Ainhoa; Rodrigues, Liliana; Aínsa, José A. (Frontiers in Microbiology, 2019)
Aminoglycoside acetyltransferases are important determinants of resistance to aminoglycoside antibiotics in most bacterial genera. In mycobacteria, however, their presence has been related partially with aminoglycoside susceptibility, and other functions can explain its widespread presence along species of genus Mycobacterium. This review is focused on two mycobacterial aminoglycoside acetyltransferase enzymes. First, the aminoglycoside 2’-N-acetyltransferase (AAC(2’)), which was identified as a weak determinant of aminoglycoside resistance in M. fortuitum, and later found to be widespread in most mycobacterial species; AAC(2’) enzymes have been related with resistance to cell wall degradative enzymes, and bactericidal mode of action of aminoglycosides. Second, the Eis aminoglycoside acetyltransferase, which was identified originally as a virulence determinant in M. tuberculosis (enhanced intracellular survival), where in fact controls production of pro-inflammatory cytokines and other pathways; relation of Eis with aminoglycoside susceptibility was found after the years, and reaches clinical significance only in M. tuberculosis isolates resistant to the second-line drug kanamycin. In both cases, AAC(2’) and Eis, given their role in mycobacterial biology, inhibitory molecules have been identified, more importantly in case of Eis inhibitors, hence evolving from potential drug resistance mechanisms into a promising future as drug targets.